Presence of anti‐HBc is associated to high rates of HBV resolved infection and low threshold for Occult HBV Infection in HIV patients with negative HBsAg in Chile. Issue 4 (28th September 2015) - Vargas, Jose Ignacio; Jensen, Daniela; Sarmiento, Valeska; Peirano, Felipe; Acuña, Pedro; Fuster, Felipe; Soto, Sabrina; Ahumada, Rodrigo; Huilcaman, Marco; Bruna, Mario; Jensen, Werner; Fuster, Francisco
Abstract : HBV‐HIV coinfection is prevalent. Frequently, anti‐HBc is the only serological marker of HBV, which can be indicative of HBV resolved infection, when found together with anti‐HBs reactivity; or present as "isolated anti‐HBc, " related to HBV occult infection with presence of detectable DNA HBV, more prevalent in HIV‐positive individuals. Regional data about this condition are scarce. Anti‐HBc rapid test has been used as screening, but its performance has not been described in HIV‐positive patients. The aim of this study was determine prevalence of anti‐HBc in HIV‐positive patients, serological pattern of HBV resolved infection and isolated anti‐HBc, evaluating presence of HBV occult infection. Assess anti‐HBc rapid test compared to ECLIA. Methods included measurement of anti‐HBc and anti‐HBs in HIV‐positive patients with negative HBsAg. Serum HBV DNA quantification and HBV booster vaccination to "isolated anti‐HBc" individuals. Detection of anti‐HBc by rapid test and ECLIA. In 192 patients, prevalence of anti‐HBc was 42.7% (82/192); associated to male gender, drug use, men‐sex‐men, positive‐VDRL, and longer time HIV diagnosis. 34.4% (66/192) had presence of anti‐HBs, mean titers of 637 ui/ml. Isolated anti‐HBc in 8.3% (16/192), associated to detectable HIV viral load and no‐use of HAART; in them, HBV DNA was undetectable, and 60% responded to HBV vaccination booster. Anti‐HBc rapid test showed low sensibility (32.9%) compared to ECLIA. These results show that prevalence of anti‐HBc in HIV‐positive individuals is high, in most cases accompanied with anti‐HBs as HBV resolved infection. Low prevalence of "isolated anti‐HBc, " with undetectable HBV DNA, and most had anamnestic response to HBV vaccination; suggest low possibility of occult HBV infection. Anti‐HBc rapid test cannot be recommended as screening method for anti‐HBc. J. Med. Virol. 88:639–646, 2016 . © 2015 Wiley Periodicals, Inc.